PANAEOLUS (AGARICALES) FROM WESTERN PARANÁ STATE, SOUTH BRAZIL, WITH A DESCRIPTION OF A NEW SPECIES, PANAEOLUS SYLVATICUS. (23rd April 2019) - Silva-Filho, A. G. S.; Seger, C.; Cortez, V. G.
Abstract : Three species of Panaeolus were collected in the western region of Paraná State, South Brazil. Panaeolus sylvaticus is proposed as a new species, based on macro- and micromorphological features and substrate (rotten wood and litter). Panaeolus antillarum and P. papilionaceus var. parvisporus, two coprophilous and widely distributed species, are also reported. All species are illustrated and discussed in detail, regarding their taxonomy, ecology and distribution. A key to the known species of Panaeolus from Paraná State is presented.